ANALISIS PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD NEGERI 22 KOTA LHOKSEUMAWE PADA PEMBELAJARAN IPAS - Muna, Zakiyatun; Fazillah, Sarah; Anwar, Nur (JURNAL PENDIDIKAN DASAR, 2025)
This study aims to apply the Discovery Learning model to improve the critical thinking skills of fifth-grade students at SD Negeri 22, Lhokseumawe City, in science learning. This descriptive qualitative study used data collection techniques such as interviews, observation, and documentation. The results indicate that the Discovery Learning model effectively improves students' critical thinking skills, as indicated by increased student engagement, self-confidence, and ability to analyze, draw conclusions, and solve problems. However, obstacles such as time constraints, differences in student abilities, and limited infrastructure remain. Teachers act as facilitators, guides, and directors in the learning process. This study recommends teacher training and the provision of adequate learning media to support the successful implementation of the Discovery Learning model Keywords: Discovery Learning, Critical Thinking, Science Learning